A qualitative inquiry into the patient-related barriers to linkage and retention in HIV care within the community setting - Adati Tarfa; Kristen Pecanac; Olayinka O. Shiyanbola (Elsevier, 2023)
Background: People with the Human Immunodeficiency Virus (PWH) experience barriers to care within the community that impedes their progress from when they discover that they are HIV positive to becoming virally suppressed. For individuals with HIV to achieve sustained viral suppression, they must be linked to care to start receiving anti-retroviral therapy and remain retained in care for continuous treatment. However, HIV surveillance data shows that many PWH are not linked to care and become lost to continuous follow-up care. Although pharmacists, PWH, and social workers interact with one another and are aware of their roles in HIV care, their perspectives on barriers to linkage and retention in care have not been investigated collectively. Objectives: Explore the perspectives of PWH, pharmacists, and social workers on barriers to linkage and retention of HIV care within the community setting. Methods: Convenience sampling was used to recruit 15 stakeholders (five PWH, five community pharmacists, and five social workers) who participated in 1-h, semi-structured interviews based on three domains of the Patient-centered Medical Home Model including (1) experiences (individual and system-level barriers to care experienced by PWH), (2) activities (social workers and pharmacists initiatives that impact adherence to care)and (3) interventions (critical issues pharmacists can address in the community to engage PWH in their HIV care). We conducted a directed content analysis based on deductive coding. To establish rigor, we focused on Lincoln and Guba's criteria of rigorous qualitative methodology: credibility, dependability, confirmability, and transferability. Similarities and divergences of themes were discussed during data analysis and agreement was reached before interpretation. Results: Emergent themes uncovered barriers to linkage and retention in HIV care as HIV-related stigma, having mental health illnesses including a history of substance abuse and social determinants of health such as homelessness, food insecurity, and insurance issues. Conclusion: The perspectives of pharmacists, social workers, and PWH can provide insight into barriers that should be identified and addressed in people living with HIV to enhance their linkage and retention in care.